The Mind-Body Problem in Samuel Alexander’s Emergentism - Fornal, Marzena (Hybris, 2018)
Among contemporary philosophers of mind prevails a view that the representatives of Classical Emergentism such as Samuel Alexander sought to create a comprehensive metaphysical system which frequently allowed existence of non-physical elements or forces. Such view, classified British Emergentism as a position contrary to commonly accepted thesis of the Completeness of Physics, contributes to discrediting it in mind-body problem debates. The main aim of this paper is to present Samuel Alexander’s metaphysics of mind and analyze its present interpretations. The primary thesis is the claim, that solution of the mind-body problem proposed by Alexander is applicable on the ground of contemporary considerations within the framework of so called Non-reductive Physicalism.